Investigation on the performance of XLPE cable insulation using tangent delta method - Misuari, Rosita (2022)
Insulation is one of the most crucial components of a cable. Failure of insulating material will lead to breakdown and consequently may cause electrical shock or injury. For that reason, analysis of insulation condition is critical to monitor the performance of high voltage cable insulation so that suitable preventive maintenance and mitigation can be planned accordingly to avoid permanent damage to the cable. In this study, the condition of medium cable (MV) cable insulation is monitored based on tangent delta or dissipation factor value from tangent delta measurement as per IEEE 400.2 Standard. The evaluation will be useful for maintenance personnel to predict the remaining life expectancy and to prioritize cable replacement as well as it is also useful for determining what other tests may be worthwhile to diagnose the cable condition. As expected, the result shows that high value of tangent delta was measured in a degraded cable insulation.